1934Penentuan Jenis dan Wilayah Prioritas Pelayanan Sistem Pengelolaan Air Limbah Domestik diKecamatan RancasariKota Bandung - Eka Wardhani; Hendra Hermawan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Rancasari Subdistrict is locatedin Bandung City,comprisesfour urban villages, encompassing 0,19 km2with six blocks of light slum areas. Slum areas are areas that tend to have more vulnerable environmental conditions due to the minimal availability of environmental infrastructure, one of which is sanitation facilities. Based on this, Rancasari subdistrict needs to determine the type of domestic wastewater management system service and priority service areas. Determination of the service type of domestic wastewater management system is determined based on Attachment 1 ofRegulation of the Minister of Public Works and Public Housing Number 4of 2017, while priority areas are determined based on Bandung City Regional Regulation Number 5 of 2022, Regional Regulations Bandung City Number 10 of 2015, and the area of slum settlements in each village. Rancasari Subdistrict is suitable foron-site system, while the main priority area is Manjahlega Village, then Mekarjaya, Derwati, and Cipamokolan.Itisnecessary to develop domestic wastewater management system facilities in the mainpriority area in the form of development of existing communal septic tanks and communal wastewater treatment facility, as well as the closure of piped domestic wastewater disposal facilityleading to the Cidurian River to stop open defecation